Health Information Seeking Behaviors and Preferences of a Diverse Multi-Lingual Cohort - Khoong, Elaine C. (Med Care, 2019)
INTRODUCTION: In order to address health disparities, it is important to understand how vulnerable individuals seek information. This study used an adapted version of the Health Information National Trends Survey (HINTS) administered in English, Spanish, and Chinese to describe the behaviors and preferences of a diverse group of vulnerable urban residents. METHODS: We administered a modified HINTS survey in English, Spanish, and Chinese and used purposive sampling to ensure 50% were non-English speakers evenly divided between Spanish and Chinese speakers and 50% of English-speakers identified as Black. We use multivariable logistic regression to determine characteristics associated with sources used for health information and preferences for delivery of health information. RESULTS: Of 1027 survey respondents (514 English, 256 Spanish, 260 Chinese), 55% had adequate health literacy, and 50% reported household income <$20,000, but 77% reported owning a smartphone. A plurality sought health information on the Internet (39%) or from a healthcare provider (36%). In multivariable analyses, smartphone ownership predicted higher odds of seeking health information on the Internet (odds ratio [OR] 2.98; 95% confidence interval [CI] 1.81, 4.91). Participants most preferred email (41%) and brochures (40%) for delivery of health information, but non-English-survey respondents were less likely to prefer email: Spanish (OR 0.30; 95% CI 0.11, 0.83); Chinese (OR 0.25; 95% CI 0.09, 0.71). Smartphone ownership predicted an email preference (OR 2.19; 95% CI 1.43, 3.36). CONCLUSION: Among vulnerable populations, smartphone ownership and language preferences impact preferences for seeking and receiving health information. These preferences need to be considered in designing health messages.